بناء مقياس الكفاءة الصحية الوقائية من الأوبئة لدى الطالب الجامعي - فرحات, احمد (University of Eloued جامعة الوادي, 2022)
تهدف الدراسة إلى تصميم وبناء مقياس الكفاءة الصحية الوقائية من الأوبئة لدى الطالب الجامعي، حيث يتكون المقياس من 44 بندا موزعة على أربعة أبعاد أساسية: بعد التغذية والصحة و يضم 13 بندا، وبعد الرياضة والصحة ويضم 09 بنود، وبعد النظافة والصحة و يضم 10بنود و بعد الحياة الاجتماعية والصحة ويضم 12 بندا، وبعد التأكد من البناء اللغوي للبنود قمنا بحساب الخصائص السيكومترية للمقياس انطلاقا من المتوسطات الحسابية والتباين ومعامل ألفا كرونباخ ومعامل سبيرمان وجيتمان وكذلك قيمة "ت" حيث تراوح معامل الصدق التكويني (0.64-0.78) أما معامل الثبات تراوح ما بين(0.71-0.76)، وكل هذه المؤشرات تدل على تمتع المقياس بصدق وثبات مرتفعين ،وهذا بعد تطبيق المقياس على عينة من الطلبة الجامعيين مكونة من 77 طالب جامعي. The study aims to design and build a scale of preventive health efficiency from epidemics for the university student, where the scale consists of 44 items distributed over four basic dimensions: the dimension of nutrition and health, which includes 13 items, and the dimension of sports and health, which includes 09 items . Concerning the hygiene and health, which consists of 10 items, and the dimension of Social life and health constitutes 12 items. After confirming and cross-checking the linguistic structure of the items, we calculated the psychometric properties of the scale based on arithmetic averages, variance, Cronbach’s alpha coefficient, Spearman’s and Gitman’s coefficient, as well as the “T” value, where the formative validity coefficient ranged (0.64-0.78).As for the stability coefficient, it ranged between (0.71-0.76). Finally, all these indicators indicate that the scale has high validity and reliability, and this is after applying the scale to a sample of university students consisting of 77 university students.